Investigation of the effects of cloud attenuation on satellite communication systems - Alawadi, Tareq A. (Cranfield University, 2012)
The aim of this project is to investigate the attenuation due to clouds at 20- 50GHz; to develop an accurate long-term prediction model of cloud attenuation applicable to slant-path links and evaluate the impact of cloud attenuation dynamics on the design of future portable EHF earth-space systems. Higher frequencies offer several advantages, for example, greater bandwidth and immunity to ionospheric effects. The EHF band is being targeted for the launch of earth-space communication systems to provide global delivery of bandwidthintensive services (e.g. interactive HDTV, broadband internet access and multimedia services, television receive-only, etc.) to portable terminal units. Since spectrum shortage and terminal bulk currently preclude the realization of these breakthrough-broadband wireless communication services at lower frequencies, a better understanding is needed in order to optimize their usage. One major obstacle in the design of EHF earth-space communication systems is the large and variable signal attenuation in the lower atmosphere, due to a range of mechanisms including attenuation (and scattering) due to clouds and rain, tropospheric scintillation caused by atmospheric turbulence and variable attenuation by atmospheric gasses. In particular, cloud attenuation becomes very significant at EHF. In this thesis, we start with an overview of literature review in the first chapter. Followed next by the theory and description of accepted-up to date- cloud attenuation models in the field (chapter 2). Then followed up by a description of the pre-processing, validations, sources and assumptions made in order to conduct the analysis of the cloud attenuation in this work (chapter 3). Afterwards, a comprehensive analysis of Meteorological and local tropospheric degradation was carried out (chapter 4). That was followed by an overview of cloud fade statistics and suggested methods to counter their effects (chapter 5). And finally the improved cloud attenuation model and the enhancement of the currently accepted cloud attenuation model (ITU-R 840.4) by terms of validating the effective temperature concept and ways of acquiring it (chapter 6).